Neutrophils Orchestrate the Periodontal Pocket - Vitkov, Ljubomir; Muñoz, Luis E.; Schoen, Janina; Knopf, Jasmin; Schauer, Christine; Minnich, Bernd; Herrmann, Martin; Hannig, Matthias (Frontiers in Immunology, 2021)
The subgingival biofilm attached to tooth surfaces triggers and maintains periodontitis. Previously, late-onset periodontitis has been considered a consequence of dysbiosis and a resultant polymicrobial disruption of host homeostasis. However, a multitude of studies did not show “healthy” oral microbiota pattern, but a high diversity depending on culture, diets, regional differences, age, social state etc. These findings deprive the dysbiosis hypothesis of its foundations. Furthermore, many late-onset periodontitis traits cannot be explained by dysbiosis; e.g. age-relatedness, attenuation by anti-ageing therapy, neutrophil hyper-responsiveness, and microbiota shifting by dysregulated immunity, yet point to the crucial role of dysregulated immunity and neutrophils in particular. Furthermore, patients with neutropenia and neutrophil defects inevitably develop early-onset periodontitis. Intra-gingivally injecting lipopolysaccharide (LPS) alone causes an exaggerated neutrophil response sufficient to precipitate experimental periodontitis. Vice versa to the surplus of LPS, the increased neutrophil responsiveness characteristic for late-onset periodontitis can effectuate gingiva damage likewise. The exaggerated neutrophil extracellular trap (NET) response in late-onset periodontitis is blameable for damage of gingival barrier, its penetration by bacteria and pathogen-associated molecular patterns (PAMPs) as well as stimulation of Th17 cells, resulting in further neutrophil activation. This identifies the dysregulated immunity as the main contributor to periodontal disease.